(ARTICLE RETRACTED) Strategi Pemenuhan Kebutuhan Ekonomi Janda Cerai Mati - Kholid Mawardi; Siti Ma’sumah; Faradiena Yulizar (Yinyang: Jurnal Studi Islam Gender dan Anak, 2018)
This article is RETRACTED, because has been publish before at JPA (Jurnal Penelitian Agama) on Vol. 18 no. 2, 2017. if you want to read and cite this article, please visit http://ejournal.iainpurwokerto.ac.id/index.php/jpa/article/view/2309.